Roferon-A: A Biologic Product of Human Interferon Alpha 2a - Wardiana, Andri; Ningrum, Ratih Asmana (BRIN, 2015)
Human interferon alpha 2a (hIFNα2a) is a cytokine regulating immune system that has been used in hepatitis and cancer treatments. It has wide biological potency covering antiviral, antiproliferative and immunomodulative activities. This mini review discusses Roferon-A as a prominent commercial product of recombinant hIFNα2a which is produced in bacterial system, Escherichia coli, as therapeutic protein for several diseases, such as chronic viral Hepatitis B, Hepatitis C, melanoma, hairy cell leukemia and renal cell carcinoma. The discussion focuses on the development process with regard to its manufacturing, preclinical and clinical studies, as well as therapeutic efficacy. In addition, we also discuss biosimilar development of hIFNα2a and its potential future developments in the context of enhancing pharmacokinetic profiles.